FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIASAAN MASYARAKAT MEMBUANG SAMPAH DI AREA TEPI PANTAI DI KANAGARIAN API-API KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - SARIAYU, PUTRI; Rianto, M.Pd, Slamet; Yuherman, SP., M.Pd, Yuherman, SP., M.Pd (STKIP PGRI Sumbar, 2014)
ABSTRACKÂ This study aims to determine the factors Habits Affecting Disposal of Waste Area Community Bank in Kanagarian Beach Fire - Fire District of South Coastal District shadow This research is a descriptive correlational . The population in this study were all families ( KK ) is located on the outskirts of the District Shaded Beach South Coastal District , amounting to 593 households . Samples were taken proportional random sampling technique with a proportion of 10 % for the sample areas so that the sample of respondents amounted to 58 families .The results of the study found that : ( a ) . The influence of environmental knowledge to the people throw garbage on the beach area at Api-Api Kenagarian District of South Coastal District shadow because of t > t table ( 2.002 > 1.672 ) , the effect of low ( r = 0.258 ) and a very small contribution ( 6.7 % ) , ( two ) . Influence of education on littering public beach area at Api- Api Kenagarian District of South Coastal District shadow because of t > t table ( 2.489 > 1.672 ) , the effect of low ( r = 0.316 and a very small contribution ( 10.0 % ) and ( three ) . influence of the number of family members towards people throw garbage on the beach area at Api-Api Kenagarian District of South coastal District shadow because of F > F table ( 5.289 > 2.712 ) , the magnitude of the effect of two variables on people throwing garbage in coastal areas in Kanagarian Fire - fire District of South Coastal District Bayang medium category ( r = 0.402 ) , whereas the contribution of including quite large ( 16.2 % ) .